Physiologically based pharmacokinetic modeling of drug–drug interactions between ritonavir‐boosted atazanavir and rifampicin in pregnancy - Shakir Atoyebi; Maiara Camotti Montanha; Ritah Nakijoba; Catherine Orrell; Henry Mugerwa; Marco Siccardi; Paolo Denti; Catriona Waitt (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Ritonavir‐boosted atazanavir (ATV/r) and rifampicin are mainstays of second‐line antiretroviral and multiple anti‐TB regimens, respectively. Rifampicin induces CYP3A4, a major enzyme involved in atazanavir metabolism, causing a drug–drug interaction (DDI) which might be exaggerated in pregnancy. Having demonstrated that increasing the dose of ATV/r from once daily (OD) to twice daily (BD) in non‐pregnant adults can safely overcome this DDI, we developed a pregnancy physiologically based pharmacokinetic (PBPK) model to explore the impact of pregnancy. Predicted pharmacokinetic parameters were validated with separate clinical datasets of ATV/r alone (NCT03923231) and rifampicin alone in pregnant women. The pregnancy model was considered validated when the absolute average fold error (AAFE) for Ctrough and AUC0‐24 of both drugs were <2 when comparing predicted vs. observed data. Thereafter, predicted atazanavir Ctrough was compared against its protein‐adjusted IC90 (14 ng/mL) when simulating the co‐administration of ATV/r 300/100 mg OD and rifampicin 600 mg OD. Pregnancy was predicted to increase the rifampicin DDI effect on atazanavir. For the dosing regimens of ATV/r 300/100 mg OD, ATV/r 300/200 mg OD, and ATV/r 300/100 mg BD (all with rifampicin 600 mg OD), predicted atazanavir Ctrough was above 14 ng/mL in 29%, 71%, and 100%; and 32%, 73% and 100% of the population in second and third trimesters, respectively. Thus, PBPK modeling suggests ATV/r 300/100 mg BD could maintain antiviral efficacy when co‐administered with rifampicin 600 mg OD in pregnancy. Clinical studies are warranted to confirm safety and efficacy in pregnancy.